122k views
5 votes
For the following geometric sequence find the recursive formula.

(1, -3, 9, ...)
an-3-an-1 where a₁ = 1
Oan= (-3) -1
an=-3-an-1 where a₁ = -1
an=-1-(-3) -1

2 Answers

4 votes

Answer:

45

Explanation:

run plus duck equals to the implement

User Peter Cullen
by
6.2k points
2 votes

Answer: the 2nd one

Step-by-step explanation: first term (a1) is -1

recursive formula goes like this

is the nth term

is the term before that

we normally have

we see each term is multipying by -3 to get next one

so that would be

where a1=-1

the 3rd option is correct except that it is the explicit formula

so answer is 2nd one.

User SilverWarior
by
5.6k points